Utilization of Cow’s Urine and Tofu’s Liquid Waste for Growth of Leucaena Leucocephala Seedlings - Yulianti Bramasto; Tati Suharti; Nina Mindawati (Jurnal Perbenihan Tanaman Hutan, 2020)
In the planting program of  lamtoro (Leucaena leucocephala), healthy and vigorous seedlings are needed, therefore, it is necessary to apply fertilizer at the nursery stage. The purpose of this study was to determine the effect of tofu's liquid waste and cow's urine on the growth of  lamtoro seedlings at aged 6 weeks until 14 weeks. The treatments consisted of control, tofu’s liquid waste (30% and 40%), and cow’s urine (50%, 60% and 70%). Treatment was given every 2 weeks. Parameters observed were height, diameter, number of leaves, biomass, toughness, shoot root ratio, seedling quality index and chlorophyll content.  The results showed that 30% and 40% of tofu’s liquid waste had a significant effect on increasing the height growth at  6 weeks and 8 weeks old seedling.  The 70% cow’s urine has a significant effect on increasing the height growth  at 6 weeks until 12 weeks old seedling. The 60% cow’s urine had a significant effect on increasing the number of leaves.